Interferon-Stimulated Gene 15 in the Control of Cellular Responses to Genotoxic Stress - Jeon, Young Joo; Park, Jong Ho; Chung, Chin Ha (Molecules and cells, 2017)
Error-free replication and repair of DNA are pivotal to organisms for faithful transmission of their genetic information. Cells orchestrate complex signaling networks that sense and resolve DNA damage. Post-translational protein modifications by ubiquitin and ubiquitin-like proteins, including SUMO and NEDD8, are critically involved in DNA damage response (DDR) and DNA damage tolerance (DDT). The expression of interferon-stimulated gene 15 (ISG15), the first identified ubiquitin-like protein, has recently been shown to be induced under various DNA damage conditions, such as exposure to UV, camptothecin, and doxorubicin. Here we overview the recent findings on the role of ISG15 and its conjugation to target proteins (e.g., p53, ΔNp63α, and PCNA) in the control of cellular responses to genotoxic stress, such as the inhibition of cell growth and tumorigenesis.